Targeting ferroptosis by poly(acrylic) acid coated Mn3O4 nanoparticles alleviates acute liver injury - Shan, Xinyi; Li, Jiahuan; Liu, Jiahao; Feng, Baoli; Zhang, Ting; Liu, Qian; Ma, Huixin; Wu, Honghong; Wu, Hao (Nature communications, 2023)
Ferroptosis, a newly characterized form of regulated cell death, is induced by excessive accumulation of lipid peroxidation catalyzed by intracellular bioactive iron. Increasing evidence has suggested that ferroptosis is involved in the pathogenesis of several human diseases, including acute liver injury. Targeted inhibition of ferroptosis holds great promise for the clinical treatment of these diseases. Herein, we report a simple and one-pot synthesis of ultrasmall poly(acrylic) acid coated Mn 3 O 4 nanoparticles (PAA@Mn 3 O 4 -NPs, PMO), which perform multiple antioxidant enzyme-mimicking activities and can scavenge broad-spectrum reactive oxygen species. PMO could potently suppress ferroptosis. Mechanistically, after being absorbed mainly through macropinocytosis, PMO are largely enriched in lysosomes, where PMO detoxify ROS, inhibit ferritinophagy-mediated iron mobilization and preserve mTOR activation, which collectively confer the prominent inhibition of ferroptosis. Additionally, PMO injection potently counteracts lipid peroxidation and alleviates acetaminophen- and ischaemia/reperfusion-induced acute liver injury in mice. Collectively, our results reveal that biocompatible PMO act as potent ferroptosis inhibitors through multifaceted mechanisms, which ensures that PMO have great translational potential for the clinical treatment of ferroptosis-related acute liver injury. Ferroptosis is involved in the pathogenesis of several human diseases and targeted inhibition of ferroptosis is promising for their clinical treatment. Here, the authors report the synthesis of ultrasmall poly(acrylic) acid coated Mn 3 O 4 nanoparticles that can act as mimics of antioxidant enzymes and scavenge reactive oxygen species, as well as potently suppress ferroptosis.